Second-leg home advantage in the Copa Libertadores da América (2005-2015) - Cesar Cavinato Cal Abad; Bruno Portella Terra; Maurício Donizete de Toledo Ananias; Rafael Alves da Silva; Marcio Alves Diniz (Universidade Estadual Paulista (UNESP), 2017)
ABSTRACT 24. Aims To investigate the home advantage (HA) in the Copa Libertadores da América (CLA) from 2005 to 2015. Methods A naive analysis was applied considering how many times a team that played the second leg at home qualified for the next round. To verify differences between home, away and draw results, the Chi-square ( χ2 ) and the Full Bayesian Significance Test were applied. For the binomial variables ("Home" or "Away"), the probability of second-leg knockout occurrence was calculated. Results The probability of second-leg HA varied from 27.27% to 63.64% suggesting fluctuations of second-leg HA during competitive phases (round of 16, quarterfinals, semi-finals and final matches) and decision forms (full time, goals away rule or penalty-shoots). Conclusion The results counteract the common belief that there is a large advantage to playing the second match of a two-leg tie at home during all competition phases. Penalty-shots seemed to affect positively the second-leg HA. Despite the causes of second leg HA in CLA need to be better investigated, soccer coaches could to use these results to think better strategies to win your knockout matches.